2017
DOI: 10.15405/epsbs.2017.05.02.199
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Education and Health Promotion in Individuals with Neuropsychological Overload Syndrome

Abstract: The supervision of health status is commonly associated with physiopatological aspects of various diseases, but also with identifying the possibilities of correcting the imbalances discovered. Increasingly nowadays, we are faced with trends and challenges for early detection or anticipation of pathological markers and for establishing how reliable are the clinical and therapeutic methods applied for a specific pathology. In this respect, the intensity of body's response to different measures should be accordin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(14 reference statements)
0
1
0
Order By: Relevance
“…A study on therapeutic education and health promotion in persons with neuropsychological overload syndrome is covered by a group of scientists led by Georgescu L. (2017). Researchers have found that even monotonous activity, lack of interest in work can lead to attention failure and memory, the appearance of fatigue.…”
Section: The Main Aspects Of Training a Future Physical Therapy Speci...mentioning
confidence: 99%
“…A study on therapeutic education and health promotion in persons with neuropsychological overload syndrome is covered by a group of scientists led by Georgescu L. (2017). Researchers have found that even monotonous activity, lack of interest in work can lead to attention failure and memory, the appearance of fatigue.…”
Section: The Main Aspects Of Training a Future Physical Therapy Speci...mentioning
confidence: 99%